2009
DOI: 10.1111/j.1398-9995.2009.02098.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of improved home ventilation on asthma control and house dust mite allergen levels

Abstract: The addition of MHRV to house dust mite eradication strategies did not achieve a reduction in mite allergen levels, but did improve evening PEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
3
49
0
Order By: Relevance
“…Aspergillus/Penicillium and Cladosporium were the most frequent fungi identified, 507 which corresponds to other studies (Flannigan et al, 2011 Cladosporium, which is an abundant outdoor fungus (Flannigan et al, 2011 properties (Verdier et al, 2014), as well as temperature and moisture levels 558 (Johansson et al, 2013), which modifies the growth of different hydrophilic and 559 xerophilic fungi (Flannigan et al, 2011 Tracking allergenic fungi with monoclonal antibodies 25 in a previous study (Wright et al, 2009 questionnaires to obtain demographic, health and behavioural data, which may 587 reduce bias when compared to self-reported questionnaires, although both methods…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Aspergillus/Penicillium and Cladosporium were the most frequent fungi identified, 507 which corresponds to other studies (Flannigan et al, 2011 Cladosporium, which is an abundant outdoor fungus (Flannigan et al, 2011 properties (Verdier et al, 2014), as well as temperature and moisture levels 558 (Johansson et al, 2013), which modifies the growth of different hydrophilic and 559 xerophilic fungi (Flannigan et al, 2011 Tracking allergenic fungi with monoclonal antibodies 25 in a previous study (Wright et al, 2009 questionnaires to obtain demographic, health and behavioural data, which may 587 reduce bias when compared to self-reported questionnaires, although both methods…”
supporting
confidence: 53%
“…This with water leaks for example (Gent et al, 2002). Only a subset of these organisms 542 infiltrating the indoor environment are capable of finding suitable growth conditions , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Tracking allergenic fungi with monoclonal antibodies 24 which will lead to the re-suspension of spores and hyphae should surfaces become 544 contaminated with fungi (Adams et al, 2013 and physical properties (Verdier et al, 2014), as well as temperature and moisture 548 levels (Johansson et al, 2013), which modifies the growth of different hydrophilic and 549 xerophilic fungi (Flannigan et al, 2011 in a previous study (Wright et al, 2009 …”
mentioning
confidence: 99%
“…10 A recent randomised controlled trial (RCT) of home ventilation demonstrated an improvement in evening peak flow readings in adults, and concluded that there may be some merit in considering ventilation in the bedrooms of children with asthma. 11 In short, empirical evidence that investment in housing benefits health is promising but limited. [12][13][14][15][16][17] This randomised controlled trial aimed to strengthen this evidence by evaluating the effectiveness and cost-effectiveness of installing ventilation systems, and improving central heating if necessary, in the homes of children with moderate or severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is some evidence that improving home ventilation and heating may be beneficial in managing childhood asthma. 3,4 In the only comprehensive published study of the economics of housing modification to improve health, Chapman et al used costbenefit analysis alongside a randomised trial to show that retrofitting houses in New Zealand with insulation yielded benefits worth up to twice the cost. 5 More than one in 10 children between the ages of 5 and 14 years in the UK has asthma, and it is the most common longterm medical condition in children.…”
Section: Introductionmentioning
confidence: 99%